Depression and Treatment of Depression in Neurofeedback - Maleki, Leila; Bafandeh, Hassan (American Scientific Research Journal for Engineering, Technology, and Sciences, 2014)
At the root of all our thoughts, emotions and behaviors lay the intricate networks of communication among the trillions of neurons within our brains. A measurement of this communication activity, like the rhythm or pulse of a flowing river, is the brainwaves. Brainwaves are tiny pulses of the electrical activity that are produced as the neurons communicate with each other. By influencing these electrical patterns, we can change the brains communication. This means that when there are patterns set up within the brain that are not working correctly there will be corresponding problems. These patterns are sometimes referred to as pathologically stable patterns. The pathological patterns can arise from a variety of possible stressors, i.e. abuse, physical trauma, emotional trauma, chronic continuous stress, worry, anxiety, etc. As a response to the perceived threat, the brain has adopted a protective patter in an effort to deal with the past (it can be just a memory) or present trauma. The brain is simply doing the best it can to protect us and enable us to deal with the real or unreal dangers and threats it perceives. A huge list of disorders can be traced to this underlying problem.